Using local ecological knowledge to assess the status of the Critically Endangered Chinese giant salamander Andrias davidianus in Guizhou Province, China - Milner-Gulland,EJ; Pan,Y (Oryx, 2015)
The Critically Endangered Chinese giant salamander Andrias davidianus, the world's largest amphibian, is severely threatened by unsustainable exploitation of wild individuals. However, field data with which to assess the salamander's status, population trends, or exploitation across its geographical range are limited, and recent field surveys using standard ecological field techniques have typically failed to detect wild individuals. We conducted community-based fieldwork in three national nature reserves (Fanjingshan, Leigongshan and Mayanghe) in Guizhou Province, China, to assess whether local ecological knowledge constitutes a useful tool for salamander conservation. We collected a sample of dated salamander sighting records and associated data from these reserves for comparative assessment of the relative status of salamander populations across the region. Although Fanjingshan and Leigongshan are still priority sites for salamander conservation, few recent sightings were recorded in either reserve, and respondents considered that salamanders had declined locally at both reserves. The species may already be functionally extinct at Mayanghe. Although respondent data on threats to salamanders in Guizhou are more difficult to interpret, overharvesting was the most commonly suggested explanation for salamander declines, and it is likely that the growing salamander farming industry is the primary driver of salamander extraction from Guizhou's reserves. Questionnaire-based surveys can collect novel quantitative data that provide unique insights into the local status of salamander populations, and we advocate wide-scale incorporation of this research approach into future salamander field programmes.